MODEL JARINGAN KERJASAMA ANTAR PERPUSTAKAAN PERGURUAN TINGGI ISLAM DI WILAYAH PROVINSI JAWA BARAT: Yunus Winoto - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Library in University have important role in “Tri dharma Perguruan Tinggi”. Its provide all type of sourch of information, both of printed and electronic to fulfill the civitas academica’s necessary. So that, they can achieve as “the hearts of educational programs”. Library have a big challenge to serve their user especially to fulfill the high expectation user about availability of source information. Its happen to almost all of library of Islamic University in Jawa Barat such as” UIN Sunan Gunung Jati Bandung IAIN Syeh Nurjati Cirebon”. That’s all the background of this research to find network model library in Jawa Barat. This research method is mix method or collaboration method to alternative single method. The result of the research are collection sourch information in Islamic University based on quantities and qualities was limited. They got all collection from donation and purchased. They want to make a network with the others university in Jawa Barat to fulfill their collection. They need collaboration such as sourch information exchange, improve the human resources and collaboration at acsess information at each library.